Ambient Seismic Noise Cross - correlation of Ambon Island and Surrounding Area, Eastern Indonesia: Preliminary Result. Issue 1 (October 2021) - Rozi Kurniawan, Muhammad Fachrul; Rosalia, Shindy; Nugraha, Andri Dian; Zulfakriza,; Sahara, David P; Muhari, Abdul; Nurdin, Andi Azhar; Widiyantoro, Sri; Puspito, Nanang T; Priyono, Awali; Lesmana, Aditya; Ardianto,; et al.
Abstract: The island of Ambon lies on complex tectonics, part of Banda Arc which is driven by the Australia – Eurasia collision. Historical earthquake data show that an earthquake resulting the greatest tsunami in Indonesia had occurred at Ambon Island. On 26 September 2019, Ambon was shaken by an M 6.5 earthquake at a depth of 10 km (BMKG). In this study, we use ambient noise data from 11 temporary stations deployed by ITB and 4 permanent stations owned BMKG which are recorded from October until December 2019. Here, we purely use the vertical component of seismogram to retrieve the Empirical Green's Function of Rayleigh waves. Cross-correlations were obtained from the daily data series and stacked the day-by-day cross-correlation data into one inter-station cross-correlation. The Empirical Green's Function is seen at the band period 1-15 s. As a part of our study, we analyze the Green's Function with frequency-time analysis (FTAN) to get Rayleigh wave group velocity. The group velocity of Rayleigh waves varies from 1.04 km/s – 3.75 km/s. Low group velocity might be indicated the presence of sediment or volcanic deposits and high group velocity might be indicated metamorphic rocks. The result of this study might give a finer velocity model of the shallow crustal beneath Ambon Island and the surrounding area.